2011
DOI: 10.1002/emmm.201100171
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of microRNA‐21 in vivo ameliorates autoimmune splenomegaly in lupus mice

Abstract: MicroRNAs (miRNAs) have been implicated in B cell lineage commitment, regulation of T cell differentiation, TCR signalling, regulation of IFN signalling, and numerous other immunological processes. However, their function in autoimmunity, and specifically in systemic lupus erythematosus (SLE), remains poorly understood. B6.Sle123 is a spontaneous genetic mouse model of SLE characterized by autoantibody production, lymphosplenomegaly, and glomerulonephritis. We identified several differentially regulated miRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(133 citation statements)
references
References 46 publications
6
124
0
1
Order By: Relevance
“…Because exosomes can affect immune cells if they deliver a specific mRNA or miRNA that can modify gene expression in a recipient cell (46,47), it may become possible to deliver Ts signature genes or inhibitors of miR-21, -155, and -30b alone or in combination to generate CD8 + Ts. Alternatively, immune deficiencies may be treated by interfering with the generation and function of Ts, inhibiting their signature genes by targeted delivery of miRNA or by blockade of the ILT3 interaction with its T cell ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Because exosomes can affect immune cells if they deliver a specific mRNA or miRNA that can modify gene expression in a recipient cell (46,47), it may become possible to deliver Ts signature genes or inhibitors of miR-21, -155, and -30b alone or in combination to generate CD8 + Ts. Alternatively, immune deficiencies may be treated by interfering with the generation and function of Ts, inhibiting their signature genes by targeted delivery of miRNA or by blockade of the ILT3 interaction with its T cell ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, 2 studies in mice have confirmed an importance of miR-21 in autoimmune T cell responses. The overexpression of miR-21 in T cells causes autoimmune cholangitis in vivo, whereas inhibition of miR-21 in T cells reverses cardinal manifestations of autoimmunity in lupus-prone mice [76,77]. These activities are linked to the ability of miR-21 to repress PDCD4, a selective protein translation inhibitor of genes involved in effector T cell survival and function [78,79].…”
Section: Mirna-mediated Control Of Cd8 + T Cell Differentiationmentioning
confidence: 99%
“…The roles of miRNAs are only beginning to be explored in CD8 + T cell-related autoimmune diseases, in which they may be involved in regulating immune responses against self-tissues. Studies in mice showed that the overexpression of miR-21 in T cells potentiates disease severity in the context of experimental autoimmune cholangitis [77], whereas inhibition of miR-21 in T cells attenuates disease severity in the setting of experimental autoimmune lupus [76]. Table 1 indicates the role of candidate miRNAs in various CD8 + T cellrelated diseases.…”
Section: Mirnas In Cd8 + T Cell-related Diseases and Mirna-targeting mentioning
confidence: 99%
“…TGF-β-путь как один из ре-гуляторов иммунного ответа является основным сигналь-ным путем, способным сдерживать CD4 + T-лимфоциты в состоянии покоя [15]. В реализации данного механизма принимает участие miR-21, ингибирование которой in vivo при системной красной волчанке способствует усиле-нию экспрессии генов, отвечающих за созревание и функ-циональную активность Т-и NK-клеток [16]. При этом TGF-β обеспечивает конвертацию pri-miR-21 в premiR-21 [17].…”
Section: заключениеunclassified